EDUKASI TENTANG UPAYA PENCEGAHAN STUNTING PADA MASA NIFAS DAN MENYUSUI DI DESA LEMINGGIR KECAMATAN MOJOSARI KABUPATEN MOJOKERTO - Meilinawati SB, Elies (Kirana Publisher, 2025)
Stunting is a disorder of child growth and development, caused by chronic malnutrition and repeated infections that last a long time, generally from pregnancy to the age of 2 years. Specific nutritional intervention efforts are focused on the First 1,000 Days of Life (HPK) group, namely pregnant women, breastfeeding mothers, and children aged 0-23 months, because the most effective stunting control is carried out in the 1,000 HPK (golden period or critical period/windows of opportunity). The existence of new information about something will provide a new cognitive foundation for the formation of a person's attitude. Audiovisuals make a very large contribution to changing people's behavior, especially in terms of information and persuasion. Community service activities aim to increase the capacity of cadres by providing knowledge about efforts to prevent stunting during the postpartum and breastfeeding periods through health education, cadres are given a pre-test questionnaire to measure knowledge before the activity begins, then health education is carried out with audio-visual media, after which a post-test is given. Based on the results of the Wilcoxon Signed Rank Test, it indicates that the median pretest rank (Mdn = 80.00) is significantly different from the median posttest rank (Mdn = 84.00), Z = 3.668, p < 0.001 means that there is a significant difference in scores between before and after health education using audio-visual media (video) for cadres or there is a significant increase in knowledge about preventing stunting during the postpartum and breastfeeding periods after health education using audio-visual media (multimedia).